Barrier Membranes for Guided Bone Regeneration (GBR): A Focus on Recent Advances in Collagen Membranes - Ren, Yanru; Fan, Lu; Alkildani, Said; Liu, Luo; Emmert, Steffen; Najman, Stevo; Rimashevskiy, Denis; Schnettler, Reinhard; Jung, Ole; Xiong, Xin; Barbeck, Mike (International journal of molecular sciences, 2022)
Guided bone regeneration (GBR) has become a clinically standard modality for the treatment of localized jawbone defects. Barrier membranes play an important role in this process by preventing soft tissue invasion outgoing from the mucosa and creating an underlying space to support bone growth. Different membrane types provide different biological mechanisms due to their different origins, preparation methods and structures. Among them, collagen membranes have attracted great interest due to their excellent biological properties and desired bone regeneration results to non-absorbable membranes even without a second surgery for removal. This work provides a comparative summary of common barrier membranes used in GBR, focusing on recent advances in collagen membranes and their biological mechanisms. In conclusion, the review article highlights the biological and regenerative properties of currently available barrier membranes with a particular focus on bioresorbable collagen-based materials. In addition, the advantages and disadvantages of these biomaterials are highlighted, and possible improvements for future material developments are summarized.